Analisis Penggunaan Campur Kode Dan Ahli Kode Dalam Kata Sambutan: Prof. Dr. Ibnu Hajar, M.Si - Sarah Evelyn Samosir; Ririn Marpaung; Anisa Berti Tua Ambarita; Hanna Sitohang; Friska Maria; Eka Putri Saptari Wulan (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2024)
Code switching and code mixing are various variations of language by a person or certain community groups, for example in schools, offices, housing and traditional markets. Traditional markets themselves can be said to be centers of interaction and transactions that allow speakers and speech partners to come from various regions with different backgrounds, statuses and mastery of languages. Differences in social backgrounds in speech communities in traditional market environments result in greater opportunities for the emergence of code-switching and code-mixing phenomena, and are interesting to study in more depth in terms of form, type and factors that influence the emergence of these phenomena.The method used in this research is descriptive qualitative to examine data by explaining or describing the data contained in the remarks. The phenomenon of code mixing is the use of two or more languages ​​in a speech. Code mixing can occur if a language speaker, when using Indonesian, then inserts regional language elements into Indonesian speech. In other words, someone who speaks using the main Indonesian language code has an autonomous function, while the regional language codes involved in the main code are just fragments without function or autonomy as a code. Meanwhile, the Code Switching Phenomenon is a speech event with a change in language use. or dialect.